The clinical effectiveness and complications of lumbar selective fenestration and concave-side fusion (LSFCF) in degenerative lumbar scoliosis (DLS) combined with lumbar spinal stenosis (LSS) - Yang Hou; Hongyang Shi; Haoyang Shi; Tianyi Zhao; Jiangang Shi; Guodong Shi (BMC Surgery, 2022)
Abstract Purpose This retrospective study was performed to analyze the clinical effects and complications of LSFCF in the surgical treatment of DLS combined with lumbar spinal stenosis (LSS). Methods A total of 26 eligible patients (mean age, 64.73 y; 17 men, 9 women) with DLS combined with LSS were included and LSFCF surgery was performed. An independent spine surgeon retrospectively reviewed the medical records and radiographs of all patients to evaluate surgical data and surgery-related complications. Preoperative, postoperative, and follow-up questionnaires were obtained to assess clinical outcomes. Results The average follow-up period of this study was 20.14 ± 5.21 months. The operation time and blood loss of patients underwent LSFCF were 129.33 ± 15.74 min and 356.13 ± 21.28 ml. The clinical effects of all patients in terms of visual analogue scale (VAS) and Oswestry disability index (ODI) have been significantly improved at the final follow-up postoperatively (P < 0.05). Complications such as infection, cerebrospinal fluid leakage, nerve injury, and internal fixation failure, etc. were not observed during the follow-up period. Conclusion The LSFCF surgery is a safe and effective treatment for DLS patients combined with LSS.